A review of soil carbon dynamics resulting from agricultural practices. (15th August 2020) - Abbas, Farhat; Hammad, Hafiz Mohkum; Ishaq, Wajid; Farooque, Aitazaz Ahsan; Bakhat, Hafiz Faiq; Zia, Zahida; Fahad, Shah; Farhad, Wajid; Cerdà, Artemi
Abstract: Literature related to the carbon cycle and climate contains contradictory results with regard to whether agricultural practices increase or mitigate emission of greenhouse gases (GHGs). One opinion is that anthropogenic activities have distinct carbon footprints – measured as total emissions of GHGs resulting from an activity, in this case, "agricultural operations". In contrast, it is argued that agriculture potentially serves to mitigate GHGs emissions when the best management practices are implemented. We review the literature on agricultural carbon footprints in the context of agricultural practices including soil, water and nutrient management. It has been reported that the management practices that enhance soil organic carbon (SOC) in arid and semi-arid areas include conversion of conventional tillage practices to conservation tillage approaches. We found that agricultural management in arid and semi-arid regions, which have specific characteristics related to high temperatures and low rainfall conditions, requires different practices for maintenance and restoration of SOC and for control of soil erosion compared to those used in Mediterranean, tropical regions. We recommend that in order to meet the global climate targets, quantification of net global warming potential of agricultural practices requires precise estimates of local, regional and global carbon budgets. We have conducted and present a case study for observing the development of deep soil carbon profile resulting from a 10-year wheat-cotton and wheat-maize rotation on semi-arid lands. Results showed that no tillage with mulch application had 14% (37.2 vs 43.3 Mg ha −1 ) higher SOC stocks in comparison to conventional tillage with mulch application. By implementing no tillage in conjunction with mulch application, lower carbon losses from soil can mitigate the risks associated with global warming. Therefore, it is necessary to reconsider agricultural practices and soil erosion after a land-use change when calculating global carbon footprints. Graphical abstract: Principal global C pools and their interaction with the soil organic carbon pool affecting soil carbon sequestration (Adopted and Modified from Lal, 2008). Image 1 Highlights: Anthropogenic activities have distinct carbon footprints. Agriculture potentially serves to mitigate greenhouse gases emissions. Tillage practices are critical to estimates the carbon budgets of various land use systems. Carbon losses from soil can be minimized by mulching with no-till practices.